1998
DOI: 10.1046/j.1365-294x.1998.00384.x
|View full text |Cite
|
Sign up to set email alerts
|

Population structure of nuclear and mitochondrial DNA variation among humpback whales in the North Pacific

Abstract: The population structure of variation in a nuclear actin intron and the control region of mitochondrial DNA is described for humpback whales from eight regions in the North Pacific Ocean: central California, Baja Peninsula, nearshore Mexico (Bahia Banderas), offshore Mexico (Socorro Island), southeastern Alaska, central Alaska (Prince Williams Sound), Hawaii and Japan (Ogasawara Islands). Primary mtDNA haplotypes and intron alleles were identified using selected restriction fragment length polymorphisms of tar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
121
0
3

Year Published

2001
2001
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 138 publications
(134 citation statements)
references
References 53 publications
10
121
0
3
Order By: Relevance
“…For species in which females are philopatric and males disperse, genetic differentiation between populations is expected to be higher when estimated using mtDNA (or another maternal marker) than using a bi-parental marker. This prediction is consistent with many genetic analyses of dispersal patterns in species known to have male-biased dispersal (eg Melnick and Hoelzer, 1992;FitzSimmons et al, 1997;Rassmann et al, 1997;Baker et al, 1998).…”
Section: Inference From the Comparison Between Markers With Differentsupporting
confidence: 87%
See 1 more Smart Citation
“…For species in which females are philopatric and males disperse, genetic differentiation between populations is expected to be higher when estimated using mtDNA (or another maternal marker) than using a bi-parental marker. This prediction is consistent with many genetic analyses of dispersal patterns in species known to have male-biased dispersal (eg Melnick and Hoelzer, 1992;FitzSimmons et al, 1997;Rassmann et al, 1997;Baker et al, 1998).…”
Section: Inference From the Comparison Between Markers With Differentsupporting
confidence: 87%
“…This general approach has been applied to different vertebrate organisms including mammals (Melnick and Hoelzer, 1992;Baker et al, 1998;Seielstad et al, 1998;Pérez-Lezaun et al, 1999;Mesa et al, 2000;Escorza-Trevino and Dizon, 2000), birds (Guttierez, 1994;Gibbs et al, 2000;Piertney et al, 2000), reptiles (Karl et al, 1992;FitzSimmons et al, 1997;Rassmann et al, 1997) and fishes (Ferguson et al, 1993;Taylor et al, 1997;Patton et al, 1997). These different studies have employed several kinds of uni-parentally inherited markers (eg mtDNA, Ylinked markers).…”
Section: Inference From the Comparison Between Markers With Differentmentioning
confidence: 99%
“…In general, humpback whales appear to be good bioindicators, reflecting what is known about environmental levels of contaminants. This lends further support to studies of humpback whale population structure, which have shown strong site fidelity of whales to feeding areas [10][11][12][13]. For example, whales that feed off the coasts of California, Oregon, and Washington are thought to form a relatively distinct feeding aggregation [10].…”
Section: Geographic Variation Of Pops In Humpback Whalessupporting
confidence: 69%
“…During their migration and winter breeding season in the tropics, humpback whales fast and depend on energy reserves accumulated in their blubber. Additionally, genetic and photoidentification studies give evidence of strong site fidelity of humpback whales to their feeding areas in both the North Pacific and North Atlantic [10][11][12][13]. Seasonal feeding behavior and fidelity to feeding regions provide the basis for using humpback whales to better understand regional patterns of marine pollution.…”
Section: Introductionmentioning
confidence: 99%
“…As mitochondrial genes are inherited from the mother, even complete mixing of males among groups will not affect population structure if females are completely philopatric (Birky et al 1983;Chesser & Baker 1996;Prugnolle & de Meeus 2002). Empirical differences in maternally versus paternally inherited genetic markers have been used to infer the amount of sex-specific migration in humans (Seielstad et al 1998;Wilder et al 2004), chimpanzees (Langergraber et al 2007) and other animals (Baker et al 1998;Natoli et al 2005;Eriksson et al 2006), so similar questions could be addressed using F ST for cultural traits. While innovation may be analogous to mutation, it is unclear how closely the various well-studied models of mutation would correspond to innovation when a trait can have one of many variants or be completely absent.…”
mentioning
confidence: 99%